Model of Empowerment Arad Nets Fisherman Towards Responsible Fisheries to Improve The Welfare of Fishermen - Sulistyowati, Sulistyowati (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
This study aims to describe the profile of fishermen, Arad's empowerment strategy, and model of empowerment of fisherman of Arad net to "responsible fisheries" to improve the welfare of fishermen in the waters of Batang Regency. This research use mixed method, that is combination of two approaches that is qualitative and quantitative approach. Techniques of data collection were obtained through questionnaire (questionnaire), FGD.Data analysis using qualitative descriptive. To determine the Model of Fishermen Empowerment Strategy usingSWOT and AHP analysis. The study was conducted in March - September 2014. Based on SWOT analysis of Strategy of Fisherman Empowerment of Arad Network to Responsible Fisheries to improve fisherman's prosperity by doing Controlling, monitoring the carrying capacity of the environment and the catch of shrimp through improving the quality of fishing resources. Where the role of fishermen determines the pattern of resource utilization and sustainable management. The success of fisheries development requires perception, participation of fishermen and the role of goverment to accommodate all needs, and future management expectations. Based on the results A’WOT is obtained : Arad fisher men empowerment model to Responsible Fisheries, through socio-ecology-based Empowerment, Co-management-based empowerment,Responsible-Fisheries Empowerment Development, Empowerment of fisherman skill to improve the welfare offishermen Keyword: Models of empowerment, fisherman Arad nets, responsible fisheries